Borderlands Identity in American Mestizos and “The Bridge Poem” - Chalise, Keshav Raj (Saptagandaki Journal, 2025)
This study examines how American mestizos are borderlands in their existence and identity and how “The Bridge Poem” depicts their situation as borderlands. 'Borderlands' and 'Mestizo' are intricately tied to the issues of existence and identity. 'Borderlands' encompasses both literal and metaphorical dimensions. It signifies physical and cultural boundary that concurrently unites and divides. Geographically, it denotes regions near country borders, which give rise to unique cultural traits. 'American mestizo,' stems from a blend of European and American Indigenous heritage, and refers to individuals of mixed descent in the U.S. It embodies a borderland culture with a blended identity shaped by Mexican and American influences. It is articulated through bilingualism and multicultural adaptation. 'Borderland culture' in American mestizos represents a distinctive identity that emerges from interactions among diverse ethnic groups. "The Bridge Poem" portrays an image repressed identity, and identity crisis which metaphorically explores the challenges of being a bridge in the borderlands, and emphasizes personal boundaries and the transformative power of self discovery. This study employs borderland theory as the tool of analysis and interpretation, and connects American mestizos and their identity as borderlands in their cultural practices and literary expressions. Of further illustration, this paper provides an extensive observation of “The Bridge Poem” as the expression of the response to borderland identity.